Abdominal Surgery in Patients With Idiopathic Noncirrhotic Portal Hypertension: A Multicenter Retrospective Study. Issue 3 (21st May 2019) - Elkrief, Laure; Ferrusquia‐Acosta, José; Payancé, Audrey; Moga, Lucile; Tellez, Luis; Praktiknjo, Michael; Procopet, Bogdan; Farcau, Oana; De Lédinghen, Victor; Yuldashev, Rustam; Tabchouri, Nicolas; Barbier, Louise; et al.
Abstract : In patients with idiopathic noncirrhotic portal hypertension (INCPH), data on morbidity and mortality of abdominal surgery are scarce. We retrospectively analyzed the charts of patients with INCPH undergoing abdominal surgery within the Vascular Liver Disease Interest Group network. Forty‐four patients with biopsy‐proven INCPH were included. Twenty‐five (57%) patients had one or more extrahepatic conditions related to INCPH, and 16 (36%) had a history of ascites. Forty‐five procedures were performed, including 30 that were minor and 15 major. Nine (20%) patients had one or more Dindo‐Clavien grade ≥ 3 complication within 1 month after surgery. Sixteen (33%) patients had one or more portal hypertension–related complication within 3 months after surgery. Extrahepatic conditions related to INCPH ( P  = 0.03) and history of ascites ( P  = 0.02) were associated with portal hypertension–related complications within 3 months after surgery. Splenectomy was associated with development of portal vein thrombosis after surgery ( P  = 0.01). Four (9%) patients died within 6 months after surgery. Six‐month cumulative risk of death was higher in patients with serum creatinine ≥ 100 μmol/L at surgery (33% versus 0%, P  < 0.001). An unfavorable outcome (i.e., either liver or surgical complication or death) occurred in 22 (50%) patients and was associated with the presence of extrahepatic conditions related to INCPH, history of ascites, and serum creatinine ≥ 100 μmol/L: 5% of the patients with none of these features had an unfavorable outcome versus 32% and 64% when one or two or more features were present, respectively. Portal decompression procedures prior to surgery (n = 10) were not associated with postoperative outcome. Conclusion : Patients with INCPH are at high risk of major surgical and portal hypertension–related complications when they harbor extrahepatic conditions related to INCPH, history of ascites, or increased serum creatinine.